Kampung Muram Sari sebagai Sentra Pengelola Administrasi Pemerintahan Unggulan di Kabupaten Merauke - Paul Adryani Moento; Hubertus Oja; Abdul Rizal (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Muram Sari Village is one of the villages in the Semangga District, Merauke Regency. This village has a population of 1,496 people with a growth rate of 0.61%. This number fluctuates from year to year, one of which is caused by the lack of population administration management so it is very important to make improvements. This condition is in line with the government program as outlined in the Law of the Republic of Indonesia Number 6 of 2014 concerning Villages that the village has the authority to regulate its own village both in terms of government administration equipment, villages, village finances, customs, village development, village assets, government agencies. village-owned businesses and even the village government itself with the aim of having strong legality. A village that has a neat government administration system certainly involves village apparatus who are proficient and have mastery of technology in managing it. Village management involves all government officials, both at the sub-district and village levels. The apparatus should have optimal capabilities in carrying out their duties in supporting the government system. It is very appropriate if the village area becomes the target of implementing government and development activities, considering that the village government is the lowest government base in the government structure which will determine the success of a comprehensive National Development.